Otimização de sobremesa vegetal saborizada com cacau (Theobroma cacao) - Lira, Camila Araújo Costa (2024)
Plant-based products are on the rise as a global trend, driven by growing health concerns, changes in eating habits such as vegetarianism and flexitarianism, and dietary restrictions such as allergies and intolerance to animal milk. Faced with these challenges, the food industry is adapting to new demands and investing in research to create functional products that meet consumer expectations. In view of the above, this study aimed to develop a vegan cocoa dessert based on chickpeas (Cicer arietinum L.), quinoa (Chenopodium quinoa willd.), sweet potatoes (Ipomoea batatas L.) and brown rice (Oryza sativa L.), and to investigate the influence of different concentrations of cocoa (Theobroma cacao) and sugar on sensory attributes. A total of 11 dessert formulations were defined using a factorial experimental design (DFC) 22. According to the response surface methodology applied in the sensory test, cocoa and sugar were optimized at 3% and 10%, respectively. The optimized vegan dessert was analyzed for its physicochemical characterization, carotenoid content, antioxidant activity, rheology, colorimetric evaluation and microbiological analysis. The vegan cocoa dessert had a pH of 6.30 ± 0.01, total soluble solids of 12.3 ± 0.05 °Brix, titratable acidity of 0.15 ± 0.01%, reducing sugar of 0.62 ± 0.06%, non-reducing sugars of 10.9 ± 0.1%, total sugar of 11.5 ± 0.10%, moisture content of 73.92 ± 0.28%, ash content of 0.44 ± 0.04%, protein of 2.94 ± 0.06%, lipids of 2.01 ± 0.16%, crude fiber of 0.53 ± 0.06%, carbohydrates of 20.69 ± 0.26%, and energy value of 112.93 ± 1.86 kcal/100 mL. The total phenolic content was 64.21 ± 1.57 mg gallic acid/100g, carotenoids of 0.53 ± 0.00 mg/mL, and antioxidant of 4.95 ± 0.39 μM trolox/mL. The color showed results for L* of 28.28 ± 0.02, a* of 11.72 ± 0.07, b* of 17.45 ± 0.15, c* of 21.02 ± 0.16, and h* of 56.11 ± 0.08. The rheological behavior aligned with the Herschel-Bulkley model, with the highest coefficient of determination (R2) of 0.9992, corroborated by the initial shear stress (29.41 ± 2.36 Pa). In the microbiological analysis, low counts of Escherichia coli/g, coagulase-positive Staphylococci/g, and absence of Salmonella spp. were detected. The combinations of all the raw materials made it possible to produce a product that is a source of nutrients, microbiologically safe and sensorially acceptable. The physicochemical characterization and rheological analysis showed that it is a viable and interesting product from a nutritional and technological point of view, and promising for future industrial scaling.